(untitled) (INCH : Journal of Infant and Child Healthcare, 2022)
In Indonesia, the effort to accelerate the improvement of community nutrition is a priority for the first 1000 days of life. The first-1000-day period of life is a golden opportunity to prevent malnutrition and its consequences. The activities carried out were specific nutrition intervention carried out by the sectors of pregnant women, nursing mothers, and babies or toddlers aged 0-23 months. Thus, one of the efforts that could be done was the health education of the first 1000 days of life using videos. Thi study aimed knowing the Effect of Health Education Using Videos About the First 1000 Days of Life on the Attitudes of Pregnant Women at Embaloh Hulu Public Health Center. The type of this research was pre-experimental design with a group of pretest & posttest designs. Data analysis used Wilcoxon test. There was a significant effect towards the attitudes before and after the health education of the first 1000 days was given (p= 0,000).